On the Negative Influence of Radiation on the Human Body - Adilov, Tulkin Turdimovich; Sarikulov, Madraim Khasanovich (European Journal of Life Safety and Stability (2660-9630), 2021)
This article discusses the spread of radiation on the globe, about the potential danger of nuclear power in the modern world, about the tests and consequences of nuclear weapons in the last century, about territories with a high level of radiation background. The regions of the globe with a high level of radiation were also studied, about the danger associated with radioactive contamination on the territory of the Tashkent region, about the negative effects of radiation on the human body, and recommendations were given on protection against radiation.